The influence of hydro-meteorological conditions on the spread of chicken cestodiasis - Bogach, M. V.; Paliy, A. P.; PerotsʼkaL. V.; PyvovarovaІ. V.; Stoyanova, V. Y.; Palii, A. P. (Regulatory Mechanisms in Biosystems, 2020)
Today one of the important problems in poultry farming and bird keeping both in homesteads and on farms is the spread of endoparasites, which cause a significant decrease in productivity and significant economic damage. Raillietinosis and daveniosis are natural focal tape helminthiases that parasitize in the small intestine of poultry. The research on chicken cestodiasis was carried out on poultry farms in the south of Odessa Region of Ukraine during 2017 and 2019. 4219 chickens of different age groups were examined, which used walking areas, with 1965 chickens – in 2017 and 2254 – in 2019. To assess the wet and dry periods with daily average temperatures above 10 °C, that is the period of active vegetation, the Selyaninov hydrothermal coefficient (SHC) was used (1937), according to which the spread of chicken cestodiasis was determined. In the south of Odessa Region, the moderate and severe period increased from four to seven months, at which the hydrothermal coefficient amounted to 0.4–0.8. The period of sufficient moisture at a hydrothermal coefficient of 1.0–1.5 decreased from three months of 2017 to two months of 2019 and the hydrothermal coefficient was not calculated for five and three months, respectively. In 2017, the hatching of cestode eggs with bird manure was recorded for nine months: from March (10.1%) to November (5.8%) with high rates in June (27.2%) and September (37.1%), while in 2019, cestode eggs were recorded in February (12.7%) and up to December (2.4%), that is, for 11 months, with the highest rates in May (41.8%) and September (43.9%). The species composition of chicken cestodes is represented by four species: Raillietina echinobothrida (74.2%), which dominates due to a longer low hydrothermal coefficient, as well as R. tetragona (9.8%), R. cesticillus (10.8%) and Davainea proglottina (5.2%). The invasion of ants with cysticercoid R. echinobothrida in 2017 amounted to 19.6%, and in 2019 – 25.9% with an intensity of 1 to 4 specimens.